Suppression subtractive hybridisation: application in the discovery of novel pharmacological targets. (1st February 2000) - Wang, Xinkang; Feuerstein, Giora Z
Suppression subtractive hybridisation (SSH) is a recently developed technology designed for identifying differentially expressed genes. Total cellular RNA isolated from two sources of tissue (such as diseased versus normal) is reverse-transcribed to generate cDNA and subtracted. One critical feature of this technique is the suppression polymerase chain reaction (PCR) in combination with subtraction. To optimise the subtraction the cDNA is digested with a restriction enzyme to generate small DNA fragments (~500 nucleotides in length). Specially designed DNA adapters are ligated onto one of the cDNA pools (usually the diseased one), which is followed by two rounds of hybridisation and PCR. Since this method is PCR-based, it is sensitive and efficient to identify genes of interest. The discovery of disease-related genes is an important step for the identification of novel therapeutic targets.